Influence of Pore Structure on Chloride Penetration in Cement Pastes Subject to Wetting-Drying Cycles - Honglei Chang; Zhiwu Zuo; Mingyue Qu; Fei Wang; Zhi Ge; Jian Liu (Advances in Materials Science and Engineering)
Copious studies have discovered a phenomenon that a chloride concentration peak appears on the surface of concrete under cyclic drying-wetting environments. In such cases, the chloride diffusion coefficient (D) obtained through directly fitting the standard error function of Fick’s second law is no longer accurate. The more reliable D obtained by the method proposed by Andrade is employed in this research to investigate the influence of pore structure on chloride penetration rate of pastes. The results show that both the effective coefficient (Deff) and the apparent coefficient (Dapp) increase with total porosity, the most probable pore size, and water absorption porosity, suggesting that the increase of the three pore structure parameters accelerates chloride penetration rate under cyclic wetting-drying condition. The increase of the three parameters makes more room available and eases the difficulty for salt solution to enter the matrix and thus leads to the augmentation of chloride transporting in matrix.